1996
DOI: 10.1002/(sici)1096-9861(19960422)368:1<1::aid-cne1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of olfactory glomeruli: Temporal and spatial interactions between olfactory receptor axons and mitral cells in opossums and rats

Abstract: Mitral cells are the primary output neurons of the vertebrate olfactory bulb and are major recipients of sensory input from the periphery. The morphogenesis of mitral cell dendrites was followed to elucidate their early spatial and temporal interactions with olfactory receptor neurons and glia during the construction of olfactory glomeruli. Monodelphis domestica, a marsupial born at an extremely immature stage, and rats were examined. Mitral cells were retrogradely labeled by application of the lipophilic dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 65 publications
3
84
0
Order By: Relevance
“…The restriction of spatial patterns of mitral cell activity may reflect the increased numbers of inhibitory interneurons (Brunjes and Frazier, 1986) and/or the pruning of olfactory receptor axons (Zou et al, 2004) and mitral cell apical dendrites during the first and second postnatal weeks (Malun and Brunjes, 1996). Nonetheless, the present results suggest that spatial coding alone may be sufficient for discrimination between monomolecular compounds in the absence of background stimuli, intensity shifts, or complex odor plume dynamics.…”
Section: Odor Coding and Odor Discrimination In Neonatesmentioning
confidence: 59%
See 1 more Smart Citation
“…The restriction of spatial patterns of mitral cell activity may reflect the increased numbers of inhibitory interneurons (Brunjes and Frazier, 1986) and/or the pruning of olfactory receptor axons (Zou et al, 2004) and mitral cell apical dendrites during the first and second postnatal weeks (Malun and Brunjes, 1996). Nonetheless, the present results suggest that spatial coding alone may be sufficient for discrimination between monomolecular compounds in the absence of background stimuli, intensity shifts, or complex odor plume dynamics.…”
Section: Odor Coding and Odor Discrimination In Neonatesmentioning
confidence: 59%
“…P7 rats were chosen because they have previously been shown to have dramatically reduced numbers of granule cells and reduced numbers of juxtaglomerular neurons, although relatively normal numbers of mitral cells (Brunjes and Frazier, 1986). Many mitral cells at this age, however, have multiple apical dendrites extending into more than one glomerulus (Malun and Brunjes, 1996). Similar results have been described in mice, with the addition that some classes of olfactory receptor neuron axons extend to more than one glomerulus at this age, before being pruned back in older mice (Zou et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in neuronal processes during experience-dependent maturation of the nervous system are common to many sensory systems. In the vertebrate visual system and olfactory bulb, excess dendritic branches are pruned during maturation (50,51). Our results indicate that temperature-induced changes in the number of MG may include both pre-and postsynaptic elements.…”
Section: Discussionmentioning
confidence: 70%
“…Although the adult SVZ-OB system retains many immature features, substantial molecular and functional changes characterize its development (Malun and Brunjes, 1996;Bailey et al, 1999;Peretto et al, 2005). Previous reports indicated that SVZ cells from adult mice transplanted into the adult SVZ migrate into the host OB and differentiate into GC and PG interneurons (Lois and Alvarez-Buylla, 1994).…”
Section: Discussionmentioning
confidence: 99%